Children with CDH are at high risk for pectus excavatum deformity and progressive thoracic asymmetry: chest wall deformities in CDH survivors - Riemer, Carolin; Lambsdorff, Luisa, Gräfin; Hutflesz, Nina; Mohr, Christoph; Weis, Meike; Weiß, Christel; Martel, Richard; Klinke Petrowsky, Michaela; Zahn, Katrin; Schaible, Thomas; Boettcher, Michael; Elrod, Julia (Journal of pediatric surgery, 2025)
Background - Congenital diaphragmatic hernia (CDH) survivors exhibit an increased risk for developing musculoskeletal anomalies. This prospective long-term cohort study investigates the characteristics, predictors and dynamic changes of different chest wall deformities in a large cohort of CDH patients. - Methods - All children diagnosed with CDH and treated at the University Hospital Mannheim from 2010 to 2023 were included. Thoracic morphology was evaluated based on 740 CT or MRI scans and statistical analysis was performed using the Mann-Whitney-U-Test, Fisher's Exact Test and Spearman's correlation. P-values<0.05 were considered statistically significant. - Results - Out of 1216 children with CDH, 548 received cross-sectional imaging examinations of the chest within the follow-up program. Mean Haller Index was 2.62 ± 0.55 and pectus excavatum deformity was present in 34.09 % of CDH patients. Thoracic asymmetry in favor of the right hemithorax was present in 45.90 % and showed a pronounced age-related progression. The severity of chest wall deformities showed a significant correlation with prenatal diagnosis, liver herniation, lower lung to head ratio and fetal relative lung volume, use of ECMO and inhaled nitric oxide, diaphragmatic patch closure and laparotomy. - Conclusion - Children with CDH show an increased incidence of chest wall deformities, including pectus deformity and asymmetry with the potential for significant age-related progression. Measurement of thoracic morphology using standardized parameters based on MRI or CT scans should be implemented as an essential component of standardized follow-up programs. Rigorous randomized, controlled intervention trials are required to evaluate whether certain therapies can alter the trajectory of these chest wall deformities.
Online verfügbar: 8. November 2024, Artikelversion: 2. Dezember 2024
Gesehen am 03.03.2025